1967
DOI: 10.1104/pp.42.12.1763
|View full text |Cite
|
Sign up to set email alerts
|

Serine Transhydroxymethylase of Cauliflower (Brassica oleracea var. botrytis L.): Partial Purification and Properties

Abstract: Sutmnmiary. Serine transhydroxymethylase (EC 2.1.2.1) has been ,purified 46-fold from caulifloxver (Brassica oleracca var. botrytis L.). The enzyme was coifnpletely dependent on the presence of tetrahydrofol,ic acid for the conversion of serine to glycine.The addition of vpyridoxal phosphate gave a large increase in the reaction rate. A double pH optimum was observed with maxima at 7.5 and 9.5. The enzyTne is specific for i,-serine. The D-'isomer is neither a sulbstrate nor an inhibitor. The Michaelis'constant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1980
1980
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Although we were not able to ascertain the location of the residual seine transhydroxymethylase activity, it was clearly extramitochondrial. The existence of two isozymes of serine transhydroxymethylase in leaves has been suggested previously on the basis of cell-fractionation studies (10,23,30) and enzymological analysis (17). Also, mutants of yeast have been described which lack mitochondrial serine transhydroxymethylase but contain a second, distinguishable enzyme which is controlled or specified by a separate gene (33 Gas-exchange Analysis.…”
Section: Methodsmentioning
confidence: 93%
“…Although we were not able to ascertain the location of the residual seine transhydroxymethylase activity, it was clearly extramitochondrial. The existence of two isozymes of serine transhydroxymethylase in leaves has been suggested previously on the basis of cell-fractionation studies (10,23,30) and enzymological analysis (17). Also, mutants of yeast have been described which lack mitochondrial serine transhydroxymethylase but contain a second, distinguishable enzyme which is controlled or specified by a separate gene (33 Gas-exchange Analysis.…”
Section: Methodsmentioning
confidence: 93%
“…this enzyme from a plant source. Previous attempts to isolate this enzyme had resulted in only partial purification due to the reported instability of this enzyme from cauliflower buds (13) and tobacco roots (15). The use of pyridoxal 5'-phosphate, 2-mercaptoethanol, and EDTA prevented the inactivation of this enzyme during purification (16).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there is some doubt on the requirement of pyridoxal 5'-phosphate for catalysis for some of the plant serine hydroxymethyltransferases (13). As most of the early work was carried out with partially purified preparations, it was difficult to draw unequivocal conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Relatively few investigations have been described on the isolation and characterization of SHMT from plants. Although SHMT from spinach (28), maize (13), soybean nodules (15), tobacco (16), castor endosperm (5), carrot, pea leaves, wheat (4), cauliflower (14), and Lemna minor (27) have been studied in some detail, the requirement of PLP for catalysis has not been clearly established. Earlier work from our laboratory on the homogeneous mung bean SHMT (18) had suggested that this enzyme may not require PLP for catalysis.…”
mentioning
confidence: 99%